Differences and Points of Reference of Ood in the Perspective of Procedural Law of the State Administrative Court and Civil Procedure Law - Elfran Bima Muttaqin; Gracesy Prisela Christy; Yusep Ginanjar; Andi Sri Rezky Wulandari; Mira Nila Kusuma Dewi (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to examine the differences and tangents related to the Object of Dispute (OOD) in the perspective of the State Administrative Court (PTUN) Procedural Law and the Civil Procedure Law. In judicial practice, the determination of OOD is crucial because it concerns absolute authority between two different judicial regimes. This research uses a normative juridical method with a legislative and conceptual approach, and is analysed qualitatively. The results of the study show that although the PTUN and the civil courts both handle legal disputes, the fundamental differences lie in the type of legal subject, the nature of the object of the dispute, and the underlying principles. On the other hand, there are potential tangents in the case of objects that are civil in nature but are issued by state administrative bodies or officials, which gives rise to jurisdictional overlaps. Therefore, it is necessary to affirm norms and harmonize the regulation of absolute authority to avoid legal dualism that is detrimental to justice seekers. This research makes a theoretical and practical contribution in strengthening the boundaries of the absolute competence of the judiciary in Indonesia